Groundwater discharge to wetlands driven by storm and flood events: Quantification using continuous Radon-222 and electrical conductivity measurements and dynamic mass-balance modelling. (15th September 2015) - Gilfedder, B.S.; Frei, S.; Hofmann, H.; Cartwright, I.
Abstract: The dynamic response of groundwater discharge to external influences such as rainfall is an often neglected part of water and solute balances in wetlands. Here we develop a new field platform for long-term continuous 222 Rn and electrical conductivity (EC) measurements at Sale Wetland, Australia to study the response of groundwater discharge to storm and flood events. The field measurements, combined with dynamic mass-balance modelling, demonstrate that the groundwater flux can increase from 3 to ∼20 mm d −1 following storms and up to 5 mm d −1 on the receding limb of floods. The groundwater pulses are likely produced by activation of local groundwater flow paths by water ponding on the surrounding flood plains. While 222 Rn is a sensitive tracer for quantifying transient groundwater discharge, the mass-balance used to estimate fluxes is sensitive to parameterisation of gas exchange ( k ) with the atmosphere. Comparison of six equations for calculating k showed that, based on parameterisation of k alone, the groundwater flux estimate could vary by 58%. This work shows that neglecting transient processes will lead to errors in water and solute flux estimates based on infrequent point measurements. This could be particularly important for surface waters connected to contaminated or saline groundwater systems.